2001
DOI: 10.2322/tjsass.44.101
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Absolute Instability in 3-D Boundary Layers: Part 2. Application to Rotating-Disk Flow.

Abstract: Rotating-disk flow is taken as a typical example of three-dimensional boundary layers. Numerical computations of localized disturbances according to the propagation theory given in Part 1 are made with a simplified system of stability equations to show if the conditions of absolute instability can be satisfied in this simple flow. The results indicate no such particular amplification of disturbances near a zero of the complex group velocity. It is also shown how initially localized disturbances propagate and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…6 as 258 and 50.6, respectively, which are slightly lower than the values R c ¼ 290, 282 and 284 for C-F mode given by Lingwood, 11) Itoh 12) and Pier, 13) and R c ¼ 69, 64 and 63 for the S-C mode by Faller,8) Balakumar and Malik 16) and Itoh,12) respectively, as well as the experimentally observed lower limits of C-F mode listed by Malik et al 17) However, the Orr-Sommerfeld equation gives R c ¼ 177 for the C-F mode, 15) which is much lower than the above non-parallel estimations. Since the present study restricts non-parallel terms only to those of the most fundamental activity in the multiple instabilities, it is reasonable that the equations proposed give a critical value midway between the parallel approach and the non-parallel attempts.…”
Section: Eigenvalue Problems For Multiple Instabilitiesmentioning
confidence: 53%
See 1 more Smart Citation
“…6 as 258 and 50.6, respectively, which are slightly lower than the values R c ¼ 290, 282 and 284 for C-F mode given by Lingwood, 11) Itoh 12) and Pier, 13) and R c ¼ 69, 64 and 63 for the S-C mode by Faller,8) Balakumar and Malik 16) and Itoh,12) respectively, as well as the experimentally observed lower limits of C-F mode listed by Malik et al 17) However, the Orr-Sommerfeld equation gives R c ¼ 177 for the C-F mode, 15) which is much lower than the above non-parallel estimations. Since the present study restricts non-parallel terms only to those of the most fundamental activity in the multiple instabilities, it is reasonable that the equations proposed give a critical value midway between the parallel approach and the non-parallel attempts.…”
Section: Eigenvalue Problems For Multiple Instabilitiesmentioning
confidence: 53%
“…Thus, various forms of stability equation system have been proposed to determine the complex dispersion relation for Kármán's rotating-disk flow (i.e., Malik 10) and others [11][12][13] ), though none of them seems to be commonly acceptable in terms of reliability and convenience. It may be natural to expect that different instabilities should be described by different stability equations, as those for Tollmien-Schlichting instability and Görtler instability of two-dimensional boundary layers along a weakly concave surface.…”
Section: Introductionmentioning
confidence: 99%
“…The critical Reynolds number she estimated was 507, under an assumption of parallel flow. However, Itoh [14,15] showed that under a slightly non-parallel-flow condition, the flow field became stable for absolute instability. Davies & Carpenter [16] in their numerical simulation showed that, in a non-parallel flow field, the velocity fluctuation consequently grew by the convective instability.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was found that the results would be different if the target of the investigation was the global instability instead of the absolute instability. Itoh [14,15] used the theoretical method and employed the vicinity of the singularity point for the zero complex group velocity. He showed that the flow field under the slightly non-parallel-flow condition was absolutely stable, and therefore concluded that applying the parallel-flow assumption is not proper.…”
Section: Introductionmentioning
confidence: 99%